2009
DOI: 10.1002/ejic.200801049
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II) Homogeneous and Heterogeneous Species and Their Application for the Ring‐Opening Polymerisation of rac‐Lactide

Abstract: Schiff base ligands (L1H-L8H) have been prepared and complexed to Zn II centres. All eight complexes have been characterised by single-crystal X-ray diffraction methods, multinuclear NMR spectroscopy and elemental analysis. It was shown that for L1H and L2H trimetallic complexes of the form Zn 3 (OAc) 4 (L1-2) 2 were isolated. However, for L3H to L7H monometallic complexes were formed, Zn(L3-7) 2 . For L8H a trimetallic complex was also isolated with the same stoichiometry as Zn 3 (OAc) 4 (L1-2) 2 but a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(22 citation statements)
references
References 45 publications
(40 reference statements)
2
20
0
Order By: Relevance
“…The ultimate goal was to isolate emissive SIMs. The salanH/salan − ligands have widely been used in transition and main group metal chemistries [66][67][68][69][70][71][72][73][74], but no Ln(III) complexes have been reported to date. The structural chemistry of the free salanH compound is exciting.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal was to isolate emissive SIMs. The salanH/salan − ligands have widely been used in transition and main group metal chemistries [66][67][68][69][70][71][72][73][74], but no Ln(III) complexes have been reported to date. The structural chemistry of the free salanH compound is exciting.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Jones et al reported novel mono-and trinuclear zinc complexes of variously substituted phenoxyimine ligands [74]. All complexes exhibited good catalytic activity in the ROP of r-LA in melt conditions at 130 • C. While monozinc species afforded atactic PLAs with moderate control (M w /M n spanning from 1.42 to 1.50), broader polydispersities and moderately heterotactic polymers were achieved in the presence of the trinuclear analogues.…”
Section: Zincmentioning
confidence: 99%
“…Zinc-based catalysts are the most promising for industrial applications due to their minimal toxicity. The successful application of zinc complexes for the ROP of LA has been extensively reviewed [31,[46][47][48][49][50]. Recently, a few zinc complexes bearing entiopure ligands were reported for use with LA polymerisation [51][52][53][54][55] and there were also some zinc complexes containing achiral ligands having afforded highly heterotactic PLA [56][57][58].…”
Section: Introductionmentioning
confidence: 99%